Tafsir Ayat Siyasah: Studi Terhadap Konsep Relasi Agama Dan Negara Perspektif Syaikh Mutawalli Asy-Sya’rawi - Syahirul Alim, Moh.; Fathurrosyid, Fathurrosyid (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2025)
The conceptual discourse on the relationship between state and religion has always been a relevant contemporary issue for humanity. On the other hand, the Qur'an as a holy book plays a synergistic role in establishing ethical principles and values that underlie the sustainability of the political system, which is manifested in the verses of siyasah. The presence of siyasah verses that are still global in nature is responded by mufassir with varied interpretations including Sheikh Muhammad Mutawalli Ash-Sya'rawi, an exegete who has also been involved in the realm of government. This study aims to explore Ash-Sya'rawi's interpretation of Qur'anic verses that discuss the relationship between religion and the state. The method used is qualitative research based on library research, with a content analysis approach to facilitate a systematic description of Ash-Sya'rawi's interpretation. The results showed that Ash-Sya'rawi's interpretation of the siyasah verses gave birth to a concept of religion-state relations that is substantive-symbiotic, where the two entities complement each other in building a harmonious socio-political order. Keywords: Siyasah Verses, Asy-Sya'rawi, Religion and State Relations.